2008
DOI: 10.1590/s1415-52732008000400003
|View full text |Cite
|
Sign up to set email alerts
|

Association between geohelminth infections and physical growth in schoolchildren

Abstract: ObjectiveThis study aims to assess the association between geohelminth infections and the physical growth of schoolchildren. MethodsThis is a cross-sectional study with the participation of 1861 children aging from 7 to 14 years who live in a municipality in the Southern region (Recôncavo) of the State of Bahia. The participants were submitted to anthropometric assessment and stool tests. Multiple logistic regression analysis was used as the statistical means to determine the association of interest. ResultsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
1
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
2
1
0
1
Order By: Relevance
“…Similarly, despite the fact that trichuriasis prevalence was at a moderate level and that the majority of infections were light, a significant association was documented between stunting and both T. trichiura infection and infection intensity. This finding aligns with observations from other studies conducted in Honduras [30], Ethiopia [31], Mexico [32], and Brazil [33, 34]. …”
Section: Discussionsupporting
confidence: 93%
“…Similarly, despite the fact that trichuriasis prevalence was at a moderate level and that the majority of infections were light, a significant association was documented between stunting and both T. trichiura infection and infection intensity. This finding aligns with observations from other studies conducted in Honduras [30], Ethiopia [31], Mexico [32], and Brazil [33, 34]. …”
Section: Discussionsupporting
confidence: 93%
“…This is due to chronic nature of Trichuris trichiura infection; in which it can stay in a human gut for more than three years [ 22 , 23 ]. Similar to this finding, other studies conducted elsewhere among schoolchildren found that infection with Trichuris trichiura is associated with stunting [ 24 - 26 ]. However, a study done in different areas of Ethiopia reported that there is no significant association between Trichuris trichiura infection and stunting [ 27 - 29 ].…”
Section: Discussionsupporting
confidence: 89%
“…The magnitude of the burden of geohelminthiasis is grossly underestimated, but it deserves to be given special attention because of its broad geographical distribution [18], its deleterious effects on nutrition [19], and its impairment of immune functions [20,21]. The important harmful factors in helminth infections include the direct pathogenic effect by the worms and the modulatory role of the parasite on the host immune system, altering the response to other antigens or pathogens and causing additional immunopathology [22].…”
Section: Introductionmentioning
confidence: 99%